Saúde do trabalhador docente do ensino superior: implicações no contexto da pandemia pela Covid-19 - Santos, Zelma José dos (2023)
Introduction: Considering the extension of restrictive measures of social isolation, due to the COVID-19 pandemic, in the years 2020 and 2021, and the progressive incorporation of digital teaching methodologies, with the transition from face-to-face modalities to online emergency remote, in the context of higher education, and, consequently, changes in teaching work, highlighting: the urgency in technological investments and digital access conditions (intellectual and financial); the use of digital technologies; the development of new skills; work overload; tolerant demands with pressure on productivity; and use of common space for professional and family activities, in addition to seclusion and deprivation of social life, it became urgent to investigate whether these conditions promoted instruction in the health of these professionals. Objective: To understand and evaluate the teaching perception of potential executives in their state of health (physical, emotional and psychological), in view of the change in the teaching method, from face-to-face to remote emergency, during the pandemic/isolation by COVID-19, linked private Higher Education Institutions (HEIs), with courses in the health area, restricted to the North Triangle region, Minas Gerais, Brazil. Methodology: Qualitative approach, through discourse analysis. The Focus Group (GF) technique was used and, additionally, a socio-professional and demographic conversation was applied. The target population of the study was professors, undergraduate courses in the health area, in the face-toface format (and emergency remote), from private HEIs, among them: medicine, dentistry, veterinary medicine, nursing and physiotherapy. The sample of the referred FG was intentional and composed of 8 (eight) professors. Results: Most professors were women, married, aged between 30 and 59 years old, without children, with more than 10 years since graduation and with a master's degree. 100% of the teachers were under the Consolidation of Labor Laws (CLT) regime and most worked up to 20 hours a week with teaching. 50% had another remunerated activity, in addition to classes and the majority have a preponderant participation in the economic life of the family. Note the change in the teachers' routine, including the increased workload. Most professors claimed to have received courses and training from HEIs to prepare for remote classes. With regard to fears and receipts perceived in the pandemic period, the fear of losing one's job was mainly reported. Regarding health, professors mentioned increased physical inactivity, poor sleep quality, increased alcohol use and mental health impairments. Conclusions: In this pandemic/isolation scenario, teachers had to reframe their knowledge and their work process, in addition to seclusion, in view of the imminence of illness due to COVID-19 and the deprivation of social interaction, with reference to the illness of teachers. We can say that there were losses in physical and mental health due to the situationand the type of work that grew and required new skills, respectively. New research is needed to seek to stimulate and strengthen public policies that aim to improve the quality of life at work for teachers.